Editorial: From Radicalism to Minority Issues (Al-Jamiah Research Centre, 2014)
This edition presents contemporary themes around Islam and Muslims in Indonesia from the issues of radicalism, online media, a Dutch scholar during colonial era, womenâs resistance to shariatization, local practice of Islamic sufism, minority group, to broader theme of the relation of religion and science. To begin with, James Adam Fenton sheds light on the way in which Indonesian society has responded to radical ideology. He argues that dialogue in open society with democratic spirit helps the society to disengage from radicalism.